The legitimacy of international legal institutions - Krehoff, B; Bernd Michael Krehoff (2011)
This thesis is about the legitimacy of political authority in general and international legal institutions (ILIs) in particular. It is divided into two parts with three chapters corresponding to each part. The first part presents an account of legitimate political authority that is based on Joseph Raz's service conception of authority but also makes some important modifications to it. The central claim of the first part is that the legitimacy of political authorities in general, as measured by the standard of Raz's Normal Justification Thesis, depends in a crucial way on the ability of the subjects to get involved –more so than Raz is prepared to admit– in the activities that are relevant in the political domain. The thesis offers a general account of legitimate political authority, i.e. one that is valid for any type of political authority. The second part, however, examines the implications of this account for the legitimacy of ILIs. These are non-state authorities, such as the World Trade Organisation or the International Criminal Court, that deal with problems of global political relevance. Because of this global approach, the subjects of ILIs (i.e. those whose reasons are to be served by the ILI) are not confined to the boundaries of regions or states, but distributed across the world. ILIs operate by creating, interpreting, and applying public international law. Despite some striking differences between ILIs and other types of political authority (particularly states), I argue that they all ought to be measured by the same standard of legitimacy, namely the Normal Justification Thesis. But I also argue that the requirements for meeting this standard of legitimacy may vary according to the type of political authority (especially with regard to the requirement of democracy).